Early Language Learning: The Impact of Teaching and Teacher Factors. Issue 4 (20th July 2017) - Graham, Suzanne; Courtney, Louise; Marinis, Theodoros; Tonkyn, Alan
Abstract: This study examined the progress in lexical and grammatical knowledge among 252 learners of French in England across the last two years of primary education and into the first year of secondary school in relation to teaching and teacher factors. It compared linguistic outcomes from two different approaches, one which emphasized oracy and the other which combined literacy with attention to oracy development. We also explored the relationship between linguistic outcomes and other teaching/teacher factors: teaching time, teacher level of French proficiency, and teacher level of training in language instruction. Learners completed a sentence repetition task and a photo description task, making small but statistically significant progress in both grammatical and lexical knowledge between test points. While teaching approach had little impact on such progress, other teaching and teacher factors did, particularly the French proficiency level of the primary school teacher and the amount of teaching time devoted to French. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .